Supervisor-Subordinate Age Dissimilarity and Its Impact on Supervisory Ratings of Employability: Does Supportive Learning Context Make a Difference? - Scholarios, Dora; Van der Heijden, Beatrice (Frontiers in Psychology, 2021)
Status incongruence resulting from a supervisor who is younger than their subordinate potentially leads to age stereotyping of employees. This article investigates the relationship between age difference and supervisory ratings of five competence-based measures of subordinate employability (Occupational Expertise, Anticipation/Optimisation, Personal Flexibility, Corporate Sense, and Balance). In addition, we consider the buffering role of a supportive learning context which allows older workers access to learning resources. Learning context is represented by duration of the supervisory relationship, perceived organizational learning climate and participation in, and application of, training and development. Using 295 dyads of employees and their direct supervisors in a Dutch building company, findings show that age dissimilarity reflecting status incongruence was related to lower supervisory ratings of Occupational Expertise (job-related competence) and Corporate Sense (social/organizational competence) regardless of learning context. Longer duration relationships exacerbated, rather than buffered, the age difference effect on some types of supervisory ratings. The implications of these findings for age stereotyping with regard to employability are considered.